The Principle of Independence of the Notary as a General Officer in Cooperation Agreements with Private Banks - Semadi, I Komang Yoga; Nurjaya, I Nyoman; Sulistyarini, Rachmi (Budapest International Research and Critics University, 2021)
This thesis is entitled